Jets from the Upper Scorpius Variable Young Star System 2MASS J16075796-2040087 via KECK/HIRES Spectro-astrometry - Emma T. Whelan; Miriam Keppler; Neal J. Turner; Ilaria Pascucci; Erika Hamden; Keri Hoadley; Min Fang (The Astrophysical Journal)
2MASS J16075796-2040087 is an ∼5 Myr young star in Upper Sco with evidence for accretion bursts on a timescale of about 15 days and, uncommonly for its age, outflows traced by multicomponent forbidden emission lines (FELs). The accretion bursts may be triggered by a companion at ∼4.6 au. We analyze HIRES spectra optimised for spectro-astrometry to better understand the origin of the several FEL velocity components and determine whether a magnetohydrodynamic (MHD) disk wind is present. The FEL high-velocity component (HVC) traces an asymmetric, bipolar jet ∼700 au long. The jet’s position angle ∼ 277° is not perpendicular to the disk. The lower-velocity emission, classified previously as a disk wind low-velocity component, is found to have more in common with the HVC and overall it is not possible to identify an MHD disk wind component. The spectro-astrometric signal of the low-velocity emission resembles those of jets and its density and ionisation fraction fall into the range of HVCs. We suggest a scenario where the accretion bursts due to the close companion power the jets past the age where such activity ends around most stars. The low-velocity emission here could come from a slow jet launched near the close companion and this emission would be blended with emission from the MHD wind.